Mediterranean: From Homer to Picasso (Assouline, 2000)
"What is the Mediterranean? A thousand and one things at the same time. Not just one landscape, but innumerable landscapes. Not one sea, but a series of seas. Not one civilization, but civilizations piled up one upon the other" (Fernand Braudel). This is all true, but the great paradox of the Mediterranean is that despite the fact that it is so varied, so difficult to encompass, it presents itself in our collective minds as a single, coherent image, a system where everything blends together to become one unified entity. The union is neither historical nor geographical: instead, The Mediterranean "whole" binds together, as with Mitteleuropa, a cultural synthesis of works and ideas, ways of thinking, customs and costumes, lifestyles, tastes and passions which give form to a specific style - a Mediterranean style. In order to explain this paradoxical cohesion, the author leads us on an exploration of the many different features that make up the geographical, philosophical and cultural identity of the Mediterranean. In particular, a quest is set for those elements that constitute what Roland Barthes referred to, in speaking of Cy Twombly's work, as the "Mediterranean effect."
English
Keywords: N5300-7418 Visual Arts- History